The cross-sectional relationship between vitamin C and high-sensitivity C-reactive protein levels: insights from NHANES database - Ding, Ning; Zeng, Zhao; Luo, Ju; Li, Keng (Frontiers in Nutrition, 2023)
Abstract Background: Ascorbic acid or vitamin C has antioxidant and anti-inflammatory properties that may impact markers of inflammation like C-reactive protein (CRP). However, studies specifically on vitamin C and high-sensitivity CRP (hs-CRP) have been scarce. Methods: We conducted a cross-sectional analysis of the National Health and Nutrition Examination Survey 2017-2018 dataset including 5,380 U.S. adults aged ≥20 years. Multiple regression models examined the relationship between plasma vitamin C and serum hs-CRP while adjusting for potential confounders. Stratified analyses and curve fitting assessed effect modification and nonlinearity. Results: An inverse association was found between plasma vitamin C and serum hs-CRP overall (β = -0.025, 95% CI: -0.033 to -0.017, p < 0.00001) and in subgroups except for the "other Hispanic" subgroup in model II (β=-0.009, 95% CI: (-0.040, 0.023), p=0.5885). The relationship was nonlinear, with the greatest hs-CRP reduction observed up to a plasma vitamin C level of 53.1 μmol/L. Conclusion: The results showed a non-linear negative correlation between vitamin C levels and hs-CRP in adults. These results suggest vitamin C intake may reduce inflammation and cardiovascular risk, but only up to 53.1 μmol/L plasma vitamin C.